Assessing multi-variable coupling effects of UV illumination, heat and oxygen on porous ZnO nanocrystalline film through electron concentration and mobility extraction1. Issue 27 (21st July 2015) - Zhang, Shasha; Xie, Changsheng; Zhang, Guozhu; Zhu, Qiang; Zhang, Shunping
<x xml:space="preserve">Abstract</x> The coupling effect of UV illumination, heat and oxygen is achieved through the important roles of photo-assisted thermal ionization and oxygen adsorption-induced interface barriers.